2005
DOI: 10.1038/nature03253
|View full text |Cite
|
Sign up to set email alerts
|

CD36 is a sensor of diacylglycerides

Abstract: Toll-like receptor 2 (TLR2) is required for the recognition of numerous molecular components of bacteria, fungi and protozoa. The breadth of the ligand repertoire seems unusual, even if one considers that TLR2 may form heteromers with TLRs 1 and 6 (ref. 12), and it is likely that additional proteins serve as adapters for TLR2 activation. Here we show that an N-ethyl-N-nitrosourea-induced nonsense mutation of Cd36 (oblivious) causes a recessive immunodeficiency phenotype in which macrophages are insensitive to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
652
6
9

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 782 publications
(699 citation statements)
references
References 24 publications
29
652
6
9
Order By: Relevance
“…In particular, it has been shown recently that several components of Gram-positive bacteria such as lipoteichoic acid can form TLR2/6 heterodimers with CD36 [38]. In addition, some TLR2 ligands, but not all, are dependent on CD36 [39]. This cooperation significantly enhances NF-kB activation and TNF-a production after TLR2 ligands bind to cells.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been shown recently that several components of Gram-positive bacteria such as lipoteichoic acid can form TLR2/6 heterodimers with CD36 [38]. In addition, some TLR2 ligands, but not all, are dependent on CD36 [39]. This cooperation significantly enhances NF-kB activation and TNF-a production after TLR2 ligands bind to cells.…”
Section: Discussionmentioning
confidence: 99%
“…Direct experiments demonstrating that bacteria experience immune privilege within the eye have not been performed, but several studies imply that this phenomenon occurs. Hoebe et al 2005 demonstrated that subcutaneous injection of 5 x 10 5 CFU of S. aureus was rapidly cleared in C57BL/6 mice within 7 days. By contrast, Engelbert and Gilmore (2005) demonstrated that C57BL/6 mice were unable to clear an intravitreal injection of as few as 5000 CFU of S. aureus, and the bacterial load within the eye increased to 2 x 10 9 CFU within 72 hours, resulting in its rapid destruction.…”
Section: Immune Privilegementioning
confidence: 99%
“…More recently, expression has been reported on hepatocytes under certain circumstances (Vosper, et al, 2001,Yu, et al, 2001,Zhou, et al, 2006 and smooth muscle cells (Lim, et al, 2006,de Oliveira Silva, Delbosc, Arais, Monnier, Cristol, & Pares-Herbute, 2006, Kwok, Juan, and Ho, 2006. CD36 plays a role in uptake of apoptotic cells (Savill, Hogg, Ren, and Haslett, 1992), shed photoreceptor outer segments , and modified lipoproteins (Endemann, Stanton, Madden, Bryant, White, & Protter, 1993,Podrez, et al,2000, and in recognition of ligands that trigger an innate immune response, including components of gram positive bacteria cell walls (Hoebe, et al, 2005,Stuart, et al, 2005 (as a co-receptor with Toll Like Receptor (TLR) 2), fibrillar amyloid β (Bamberger, Harris, McDonald, Husemann, & Landreth, 2003,El Khoury, et al, 2003, which is a constituent of Alzheimer plaque, and resembles fibrillar amyloid protein (Medeiros, et al, 2004), that may occur in atherosclerotic plaque. In addition to facilitating fatty acid transport into adipocytes and cardiac and skeletal muscle (and perhaps other cells), CD36 was recently shown to be a sensor for fatty acids in taste buds, eliciting a secretory response in the gut (Laugerette, et al, 2005).…”
Section: Cd36 Structure and Expressionmentioning
confidence: 99%
“…CD36 recognizes and binds apparent pattern motifs which are often non-protein repetitive molecules, such as found on the outer membranes or walls of bacteria. Hoebe, et al (2005) characterized a recessive mutation in N-ethyl-N-nitrosurea (enu) mutated mice which did not respond to some TLR 2/6 ligands, and showed it to be within the CD36 gene, resulting in absent expression (oblivious mice). Interestingly, they found that CD36 was a necessary co-receptor for TLR 2 ligands containing diacylglycerides but not triacylglycerides.…”
Section: Cd36 Ligands and Functionsmentioning
confidence: 99%